The synergic use of the High Power Laser Therapy and Glucosamine sulfate in Knee osteoarthritis: A Randomized Controlled Trial - Ammendolia, Antonio; Marotta, Nicola; Marinaro, Cinzia; Demeco, Andrea; Mondardini, Paolo; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: To determine the efficacy of the synergistic use of High Power Laser Therapy (HPLT) with glucosamine sulfate (GS) in knee osteoarthritis.Methods: This 2-arm randomized controlled trial (RCT) enrolled 90 subjects (M=53, F=37, y= 55±11.2) and randomly allocated using a stratified sampling method in experimental group (A) with HPLT+GS 1500mg (GS - Dona®, Rottapharm, Monza, Italy) (n=45) or in a control group (B) with HPLT + placebo (n=45). Results: VAS score in Activities of day Living (ADL), Standardized stair climb test (SSCT), Zohlen’s sign (RASPING) and Rabot test were used, to evaluate patients at the beginning of the study (T0), at 2 months (T1) and at 6 months (T2). In the mean scores for VAS in ADL, SSCT, RABOT and RASPING at T1, no significant differences were found between the experimental and the control group with paired T and ANOVA test. But significant differences between groups (p